Express bus consortium : towards achieving the economies of scale case study : Transnasional Express Sdn. Bhd. / Nik Husna Nik Abdullah - Nik Abdullah, Nik Husna (1996)
Public transportation has become important today as to move people from one place to another place. One of the most popular public transportation is express bus service. The express bus service connecting two points over 100 kilometers being provided by a comfortable coach, as it takes a long journey. Nowadays, many operators exist to operate the express bus service as it seems to bring a profitable income, thus increase the competition among operators. Towards solving the problem, government has made a decision to form two consortiums to lead the industry. Two major companies has been chosen to lead the consortia, namely Mara Holding Sdn. Bhd (Transnasional Express Sdn. Bhd.) and Park May Berhad. The consortiums to achieve the government's objective towards providing an efficient and effective public transportation to the public.